PEMBELAJARAN PROBLEM SOLVING DI PESANTREN PERSPEKTIF PSIKOLOGI ISLAM - Amar Ma'ruf Ma'ruf; Abdul Muhid (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
In an education process, there are several components that complement each other, ranging from methods to institutional HR issues and others. Learning application methods that can attract sympathy and focus students in learning are the main capital for the success of the learning process, therefore Problem Solving is a parable of methods and learning that encourages students to think and utilize thoughts/insights without focusing on the quality of their ideas. This study uses a qualitative method with a library research approach. Data collection techniques using documentation. The data sources of this research are books and journals related to learning Problem Solving in Islamic boarding schools and the development of psychological theories. While the findings of this study are students are expected to be more effective and efficient because they not only listen to the teacher's explanations, but also actively solve the problems they discuss, therefore a teacher must effectively motivate students to try to voice their ideas. Students can solve problems progressively using problem solving learning, producing appropriate and fast problem solving results.